Physical activity during recreational youth sport: does coach training have an influence? - Schlechter, Chelsey R. (Kansas State University, 2015)
Background: This study examined youth moderate-to-vigorous physical activity (MVPA) levels during flag football practice and compared youth MVPA in practices led by trained or untrained, and by experienced or inexperienced coaches. Methods: Boys (n = 111, mean age= 7.9 ± 1.2 years) from 14 recreation flag football teams wore an accelerometer during two practices. Each team's volunteer head coach reported prior training and coaching experience. Results: Mixed-model team-adjusted means showed the proportion of practice time spent in sedentary (13 ± 1%), MVPA (34 ± 2%), and vigorous (12 ± 1%) activity. Practice contributed ~20 minutes of MVPA towards public health guidelines. There was no significant difference in percentage time spent in MVPA between teams with trained (mean = 33.3%, 95% CI = 29.4%, 37.2%) and untrained coaches (mean= 35.9%, 95% CI = 25.5%, 42.4%) or between experienced (mean = 34.1%, 95% CI= 30.2%, 38.0%) and inexperienced coaches (mean = 33.8, 95% CI = 27.9%, 39.7%). Conclusion: Although sport provides a setting for youth to be physically active at a moderate to vigorous level, two-thirds of practice was spent sedentary or in light activity. Having participated in a coach training program was not associated with higher MVPA. Further research is needed to inform volunteer coach training programs that provide coaches with skills necessary to increase the percentage of practice time spent in MVPA.
Keywords: Physical activity; Sport; Public Health (0573)